ISOLASI DAN IDENTIFIKASI GLIKOSIDA STEROID DARI DAUN ANDONG (Cordyline terminalis Kunth) - Bogoriani, N. W. (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation and identification of two steroid glicosides have been conducted from Andong leaves (Cordyline terminalis Kunth). The isolate (4,0 mg white amorphous solid) was obtained after a series of chromatographic separations. Identification of the isolate using mass spectrometry with positive electrospray showed MW 868 as calculated from the ion peaks of m/z 891[M + Na]+, and 869[M + H]+. The ion peaks of isolate at m/z 727[(M + Na) - 164]+, 723[(M + H) - 146]+, 705[(M + H) - 164]+, and 413 [(M + H) - 456]+ of its fragments indicated the presence of three sugars (two terminal sugars and one central sugar) from methylpentose moeity (each of MW 164) linked to an agyicone. Proton magnetic resonance spectrum of the isolate in pyridine-d5 showed characteristic proton signals for three steroid methyls (two angular methyls and one secondary methyl) at d 1.37 (s), 0.85 (s) and 1.06 (d, J = 6 Hz); and one methyl group for C25 at d 0,66 ppm (d, J=6 Hz); an ethylene group at d 5.51 ppm (br d, J = 5.7 Hz); signals of the protons linked to C26 at d 4.13 and 3,49 ppm (each br d, J = 9,3 Hz and 9 Hz), and three anomeric protons at d 6.43 ppm (br s); 5.56 ppm (br s) and 4.57 ppm (d, J = 7.0 Hz). From the above data it can be assumed that the isolate is a spirostan steroidal glicoside.
Keywords: isolation, identifiCation, Cordyline terminalis Kunth, Liliaceae